Need Assessment for the Development of A Training Model for Coping Learning in Kindergarten - Muthmainah Muthmainah; Budi Astuti (Jurnal Pendidikan Anak, 2024)
Coping learning is critical for fostering children's ability to cope with their problems. This study explored the issues and requirements for creating a training model for coping learning in kindergartens in Yogyakarta. Following Borg and Gall's exploration stage of the research and development approach, this research analyzed four (4) principals' and five (5) educators' input. During the exploration stage, data on coping learning was collected through observations and interviews. Interactive analysis was employed as the data analysis technique.  The findings revealed some issues, specifically: 1) educators lack the necessary knowledge and skills to implement coping learning effectively, 2) the lack of a Standard Operating Procedure (SOP) for coping learning resulted in a haphazard approach to its implementation, 3) educators have limited knowledge and ability to manage children's emotional and behavioral problems, 4)  insufficient coping-based learning resources, and 5) certain parenting practices prevent children from developing coping skills. The needs assessment results will then be used to create a training model, which will then be submitted for expert judgment and field testing to determine its effectiveness.